2020
DOI: 10.1002/lary.28552
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Smoking on Olfactory Dysfunction in 3,900 Patients With Olfactory Loss

Abstract: Objectives/Hypothesis The association between smoking and olfactory loss remains a conundrum. Prior studies have found negative and positive effects of smoking on olfactory function in the general population. However, smoking cessation seems to improve both rated and measured olfactory function. The purpose of this study was to investigate the olfactory function and smoking habits in patients with olfactory loss caused by different etiologies to unveil underlying patterns related to smoking. Study Design Retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
4
10
0
3
Order By: Relevance
“…Sin embargo, el cese del hábito tabáquico parece mejorar la función olfativa. Un estudio que incluyó a 3.900 pacientes con pérdida olfativa, 521 fumadores activos y 316 exfumadores, concluyó que los pacientes con tabaquismo activo no tenían una función olfatoria significativamente menor 6 .…”
Section: Etiología De La Pérdida De Olfatounclassified
See 1 more Smart Citation
“…Sin embargo, el cese del hábito tabáquico parece mejorar la función olfativa. Un estudio que incluyó a 3.900 pacientes con pérdida olfativa, 521 fumadores activos y 316 exfumadores, concluyó que los pacientes con tabaquismo activo no tenían una función olfatoria significativamente menor 6 .…”
Section: Etiología De La Pérdida De Olfatounclassified
“…Especialmente utilizadas en el ámbito de la investigación, se han desarrollado pruebas objetivas en las que los datos no dependen de la subjetividad del paciente [5][6][7] . Entre ellas destacan las exploraciones electrofisiológicas del olfato (electroolfatograma, potenciales evocados olfatorios), las pruebas de imagen estructurales y funcionales olfatorias, y biopsias de la región olfativa.…”
Section: Pruebas Objetivasunclassified
“…A recent study included 3,900 patients with olfactory loss; 521 were current smokers and 316 former smokers. They concluded that patients with a history of smoking did not have a significantly lower olfactory function [25].…”
mentioning
confidence: 99%
“…A study that included 3900 patients with olfactory loss, 521 active smokers and 316 ex-smokers, concluded that patients who were active smokers did not have significantly lower olfactory function. 6 …”
Section: Loss Of Smell Aetiologymentioning
confidence: 99%
“…Objective tests are especially used in research, and some have been developed in which the data does not depend on patient subjectivity. 5 , 6 , 7 Tests to be highlighted include the electrophysiological tests of olfaction (electro-olfactogram, olfactory evoked potentials), olfactory structural and functional imaging tests, and biopsies of the olfactory region. The limitations are that these tests can only be performed in highly specialised centres; furthermore, they do not discriminate between the different causes of OD, and they do not provide information on the possible location of the damage.…”
Section: Smell Testingmentioning
confidence: 99%